The Quality of Fresh and Frozen Semen and its Correlation with Molecular Weight of Seminal Plasma Protein in Bali Cattle - H. Iskandar; H. Sonjaya; R. I. Arifiantini; H. Hasbi (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study evaluated the quality of fresh and frozen semen of Bali cattle and its correlation with the molecular weight (MW) of seminal plasma protein. This study collected semen from 10 bulls aged 5–10 years using an artificial vagina and evaluated the samples macroscopically and microscopically. Two batches of frozen semen obtained in 2020 and 2021 were also analyzed. The frozen semen samples were thawed at 37 °C for 30 seconds. The sperm motility, viability, intact plasma membrane (IPM), and sperm abnormalities were investigated. The concentration of the seminal plasma proteins was determined using the Bradford method, and the proteins were characterized using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (1D-SDS-PAGE). Additionally, the gels were stained with Coomassie brilliant blue, and the MWs of the proteins were determined using MW markers. The sperm motility, viability, and abnormalities of fresh semen varied significantly among the bulls (p<0.05); however, sperm IPMs among the bulls were similar (p>0.05). No differences in sperm motility after freezing were found among the bulls. However, the sperm viability, abnormality, and IPM varied among the bulls. Meanwhile, the seminal plasma proteins contained bands with different MWs. No difference in the expression of protein bands between bulls. Linearity analysis showed that sperm motility (r= 0.281), viability (r= 0.189), abnormalities (r= 0.141), and IPM (r= 0.173) were positively correlated with the protein bands at each MW (p<0.05). The results conclude there was a positive correlation between the MW of the protein marker and the same protein expression levels in Bali bulls. Therefore, the band intensity of Bali cattle seminal plasma proteins can be used as a biomarker for selecting superior Bali bulls.